EVALUASI SIFAT MEKANIK KOMPOSIT BIJI KAPUK RANDU BERPENGUAT RESIN POLYESTER DENGAN PEMBANDING BRAKE SHOES DAN BRAKE PAD PABRIKAN - Wahyu Eko Purnomo; Gunawan Dwi Haryadi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2015)
Brake is a vehicle component that serves to slow or stop the vehicle comfortably. Composite is a kind of new material engineered consisting of two or more materials where each material properties different from each other both chemical and physical properties and remain separate from each other and the material. In the present study the researchers wanted to know the effect of weight percent polyester that are added to the ash kapok seed as the composite material is applied to the motor vehicle brake shoes in the review of the nature of the wear rate, flexibility, and hardness. From the test results in getting the results of the wear rate is highest in the specimen 3 with a polyester resin composition ratio of the smallest is 7: 3 between ash and polyester resin, while the lowest wear rate is the ratio of specimen 2 7: 9 between ash and polyester resin. Value flexibility composite brake shoes kapok seed is highest in the specimen 1 with the composition ratio of 3: 2 between ash and polyester resin, while the lowest flexibility is a specimen 2 in the ratio of polyester resin compositions, most notably 7: 9 between ash and polyester resin. The highest hardness value is the specimen with composition 7: 9 Abu + Polyester Resin is 78.62 HV. While most low hardness values are specimens with composition 5: 3 Abu + Polyester Resin is 67.21 HV.